Development of nanoparticle sensors for the detection and quantification of Swine DNA in Mixed biological and commercial samples for Halal authentication - Md Eaqub Ali (School of Microelectronic Engineering, 2011)
To develop, characterize, and test nanobiosensor probes for the detection and quantification of shorter swine DNA markers of mitochondrial origins in mixed biological and commercial samples for Halal authentication.